Rheumatic Fever and Rheumatic Heart Diseases in Bangladesh: Challenges and Remedies (Cardiovascular Journal, 2018)
In the 21st century, Rheumatic fever (RF) and Rheumatic heart disease (RHD) are neglected diseases of marginalized communities. Globally, RHD remains the most-common cardiovascular disease in young people aged